Novel market conditions and marketing consequences in the hungarian guided hunting sector - Magyar, Zoltán (Acta Agraria Debreceniensis, 2008)
In Hungary the operating medium of game management and the guided hunting sector is undergoing such a radical change nowadays that on the one hand it considerably influences the profit-producing ability of the sector, and on the other hand it sets the actors of the industry new challenges and opportunities. If the Hungarian hunting industry, which has a traditional past, also wishes to preserve its position in this changed business medium, it is essential that the new situation be thoroughly assessed, and the value-oriented marketing attitude be adapted. The phenomena presented in this essay discuss the consequences and causes of the appearance of new service providers regarding the supply side, and the content changes of the consumer group and the modification of earlier consumption preferences and their causes on the demand side. The changing of the two media jointly generate the adaptation of the value-oriented service - marketing concepts, by using which the areas to be developed and deemed as the narrow cross-section of consumer decisions can be determined. After specifying the target group specific marketing properties of the aove-mentioned – prestige – service, such services of high utility content can already be established successfully that can be positioned as a proper alternative for the new consumer group of higher value expectation. On the other hand, the employment and profitability indexes related to this sector may considerably be improved.